Pedagogical Values of Psychodrama in Children's Theatre Performances (Eurasian Journal of Humanities and Social Sciences, 2022)
The Children's Theatre includes different styles such as singing theatre, brides, dramatic theatre and shadow imagination... so we must take into account these forms, during the process of directing and acting the privacy of children, and in order to deliver the educational message properly and influentially we need therapeutic characters on the stage making it an important means of raising the child and developing his personality and modifying hisbehaviour by influencing drama therapy such as This character has been used in the majority of theatrical performances with psychological problems. Here, the educational values of Psychodrama must be invested in children's theatre shows. Educational values are not attained and children's instructions and treatment are conveyed. The researcher has drafted a title for her tagged research: What are the educational values of Psychodrama in children's theatre performances.Chapter 1 also identifies the importance of research and its beneficiaries and identifies the objective of research that is defined in the disclosure of: educational values of psychodrama in children's theatre performances. The researcher also identified the basic terms dealt with in the research.The second chapter was devoted to the theoretical framework of research and previous studies in it. It included two studies, dealing with the first:, Psychodrama and the second research: the children's theatre and educational values of psychodrama. Some relevant studies were also used and discussed and then identified some indicators produced by the theoretical framework and previous studies.The third chapter identified the methodology and procedures of the research and identified the research community, which includes (6) theatrical performances. The researcher selected a sample of her research at random (2), which is in line with the research objective, a play (rainy colors – bahlol Al-akual ).To measure the research objective, the researcher discussed and described the psychodrama-themed scenes in each of the research sample, to reveal the achievement of the goals for which they were set, to reach the results, and by presenting the findings, the researcher reached the most important conclusions and therefore the recommendations and proposals made by the researcher.